Open service-oriented architecture for transport protocols. (29th March 2011) - Exposito, Ernesto; Chassot, Christophe; Lamolle, Myriam; Gomez, Jorge; , Nicolas Van Wambeke
The accelerated progress in internet technologies has widely increased by one hand the diversity of distributed multimedia applications (i.e., IPTV, VoIP, VoD, video-conferencing, etc.) and by the other hand the available network services (i.e., high speed, wireless, mobile, etc.). This important evolution of application and network layers has deeply impacted the role of the traditional transport layer. Moreover, continuous enhancements and new developments of transport protocols have made quite complex for applications the selection of the adequate service for a particular network environment. Furthermore, most of new transport developments have not followed well-known software engineering approaches aimed at facilitating code reusability, integration and interoperability. This paper proposes the Open-Service Oriented Architecture for Transport Protocols (OSOATP) aimed at making easier for applications the selection of the adequate transport services. OSOATP is built following service-oriented and service-component architecture approaches in order to allow smooth integration and dynamic composition of reusable transport components. Studies intended to illustrate the benefits of this architecture are also presented.